The multiple uses of water derived from managed aquifer recharge systems in Kenya and India - Parker, Alison; Nyangoka, Justus; Rodrigues, Inês; Yadav, Basant; Le Corre Pidou, Kristell; Campo Moreno, Pablo; Quinn, Ruth (IWA Publishing, 2022)
‘Multiple-use services’ (MUS) takes into account the fact that households use water for both domestic and for productive uses. This paper is the first to determine how managed aquifer recharge (MAR) systems are a form of MUS. Two cases were studied in India and in Kenya. In the Kenyan case, sand dams are the form of MAR, and in India check dams and infiltration ponds of various scales are used. Through observations, interviews, and water quality data, it is possible to describe how the communities access the water from these infrastructures in multiple ways for different uses, according to their water needs and the characteristics of the different access points. MAR involves harvesting rainwater and retaining run-off water into the dry season thus increasing the amount of available water and enabling diversification of water uses. It should therefore be considered as an option by water managers aiming to develop water resources meeting both the domestic and productive needs of communities.
Keywords: manager aquifer recharge; multiple-use services; percolation ponds; sand dams; water harvesting